The lure of images : a history of religion and visual media in America - Morgan, David, 1957- (London ; New York : Routledge, 2007)
David Morgan explores the cultural marketplace of public representation, showing how American religionists have made special use of visual media to instruct the public, to practice devotion and ritual, and to form children and converts. Examples include: studying Jesus as an American idol; Jewish kitchens and Christian Parlors; Billy Sunday and Buffy the Vampire Slayer; Uncle Tom's Cabin and the anti-slavery movement. This unique perspective reveals the importance of visual media to the construction and practice of sectarian and national community in a nation of immigrants old and new, and the tensions between the assimilation and the preservation of ethnic and racial identities. As well as the contribution of visual media to the religious life of Christians and Jews, Morgan shows how images have informed the perceptions and practices of other religions in America, including New Age, Buddhist and Hindu spirituality, and Mormonism, Native American Religions and the Occult. - Publisher.
The aura of print -- Religious visual media and cultural conflict -- Consumption and religious images -- Parlors and kitchens: domestic visual practice and religion -- Pictorial entertainment and instruction -- Seeing in public: America as imagined community -- Facing the sacred: image and charisma -- Back to nature.
Includes bibliographical references (pages 294-300) and index.
Keywords: Mass media in religion -- United States -- History; Mass media -- Religious aspects -- Christianity -- History; Mass media -- United States -- History